2022
DOI: 10.1021/acsaelm.1c01108
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Highly Reversible Thermochromic Layered Perovskite [(CH2)2(NH3)2]CuCl4 Crystal Coupled with an Inverse Magnetocaloric Effect

Abstract: The layered, lead-free hybrid perovskites are superior in organic electronics compared to their three-dimensional (3D) counterparts due to their facile synthesis and promising stability to various environmental conditions. To learn more about the multifunctional side of such materials, a layered perovskite (EDA)­CuCl4 [EDA is (CH2)2(NH3)2] crystal was grown in solution and crystallographically characterized by single-crystal X-ray diffraction. The crystal is thermally very stable and exhibits a high reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…OIH halides incorporating Mn 2+ ions in an octahedral coordination exhibit intense red emission because of the 4 T 1g (G) → 6 A 1g (S) transition. , In contrast, manganese centers in a tetrahedral coordination display green emission stemming from the 4 T 1 (G) → 6 A 1 (S) transition . Further, copper­(II)-based OIH halides demonstrate multifunctional properties. This Jahn–Teller active cation undergoes structural transformation resulting in a change in emission color . Hence, multifarious approaches have been made to design OIH halides to incorporate manganese­(II) ion in different coordinations, mainly by varying the organic cations, , but OIH halides manifesting different coordination geometry without changing the organic cations are rare. , We attempted to synthesize new OIH halides with different Mn 2+ coordination geometry to explore fascinating photophysical and magnetic properties, which we report in this article.…”
Section: Introductionmentioning
confidence: 99%
“…OIH halides incorporating Mn 2+ ions in an octahedral coordination exhibit intense red emission because of the 4 T 1g (G) → 6 A 1g (S) transition. , In contrast, manganese centers in a tetrahedral coordination display green emission stemming from the 4 T 1 (G) → 6 A 1 (S) transition . Further, copper­(II)-based OIH halides demonstrate multifunctional properties. This Jahn–Teller active cation undergoes structural transformation resulting in a change in emission color . Hence, multifarious approaches have been made to design OIH halides to incorporate manganese­(II) ion in different coordinations, mainly by varying the organic cations, , but OIH halides manifesting different coordination geometry without changing the organic cations are rare. , We attempted to synthesize new OIH halides with different Mn 2+ coordination geometry to explore fascinating photophysical and magnetic properties, which we report in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Thermochromism in hybrid materials is often coupled with the structural distortions of a certain type and is most frequently evident as continuous thermochromism. However, there are still many challenges in this respect, which are demonstrated by examples of reversible and irreversible thermochromism of the layered tetrachlorocuprates [ 22 , 23 , 24 , 25 , 26 , 27 ]. Particularly, it is not clear what structural changes lead to such strong and ubiquitous effect in this class of materials.…”
Section: Resultsmentioning
confidence: 99%
“…Among 2D HOIHs Cu(II)-based ones have lately shown considerable potential, as it was demonstrated that they can be considered as equally efficient but environmentally more benign options to the Pb-based HOIHs which were typically engaged in photovoltaic applications [ 16 , 17 ]. On the other hand, Cu(II)-based HOIHs can display different magnetic-based phenomena like chiral ferromagnetism or multiferroic behavior [ 18 , 19 , 20 , 21 ], along with the stimuli-responsive behavior like thermochromism [ 22 , 23 , 24 , 25 , 26 , 27 ], which extends the paths of their application. While trying to comprehend the intimate structure–property relationship in HOIHs, one becomes aware of a multitude of factors that are coupled with the particular structural type, and subsequently its properties and potential for application.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, replacing lead with low toxic or nontoxic ions, such as Sn, Ge, Cu, Bi, and Sb, will result in environmentally friendly perovskites with outstanding photoelectric properties, which has been revealed by pioneering studies (Figure ). For example, Seo et al demonstrated 2D perovskites (DA) 2 MnCl 4 (DA = decylammonium) and (NA) 2 CuBr 4 (NA = nonylammonium) with narrow hysteresis and pressure-sensitive order–disorder phase transitions (Figure ).…”
Section: Perovskitementioning
confidence: 99%